(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Research results allow to assert that educational activities in out-of-school hours provide pupils of 8-9 forms with ample opportunity by including methods of psychological influence, having a creative character and non-strict regulation. In researching it was determined the connection of personal development and the features of education in non-regulation creative activity. The important feature for the decision of problems of formation of the person of the senior pupil is definition of a place remedial and productive in motivation of work in out-of-school hours.